Quantitative Analysis of Hope, Gratitude, and Satisfaction as Predictors of Psychological Well-Being in Medical Students (Medical Forum Monthly, 2023)
Objective: The objective of the study was to measure hope, gratitude and satisfaction with life as indicators of psychological well-being in medical students.Study Design: Quantitative Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, Islamic International Medical College, Rawalpindi from 15th April 2023 to 15th September 2023.Methods: A total of 246 students of a medical college in Pakistan participated in this study. 132 were male (56%) and 114 were female (46%). All the students answered a well-being survey comprising a Gratitude Questionnaire-Six Item Form (GQ-6), The Flourishing Scale by Diener et al. (2010), the Satisfaction with Life Scale, devised by Diener et al. (1985), and a Gratitude Scale developed by Kardas and Yalçın (2019). Data was analyzed using SPSS version 21.Results: Gratitude predicted 49.7% of the variance in well-being alone; life satisfaction predicted 54%, and hope predicted 96%. Pearson correlation was positive and Gratitude was most close to well-being and it was followed by the variables; life satisfaction and hope.Conclusion: Gratitude stands out as a critical predictor of well-being, playing a pivotal role in nurturing a positive outlook. This is relevant for medical students, who can harness gratitude to alleviate stress and navigate daily hurdles more smoothly.